(untitled) (Journal of Renal and Hepatic Disorders, 2017)
Vitamin D deficiency is common in advanced liver disease but its clinical significance remains controversial. The aim of this study was to examine the correlation of 25-hydryoxy vitamin D levels with liver disease severity and calcium levels in adults with cirrhosis. This cross-sectional study included 180 adults with cirrhosis enrolled in a clinical cohort study at a single university hospital. The mean age was 58.8 (±9.2) years, and cirrhosis was attributed to alcohol use in 27.2%, hepatitis C in 35.0%, non-alcoholic steatohepatitis in 27.2%, and both alcohol and hepatitis C in 10.6%. The median model for end-stage liver disease-sodium(MELD-Na) score was 12.0 (interquartile range 9.0–16.0), and mean serum albumin levels were 3.4 (±0.7) gm/dl. Median serum 25-hydroxyvitamin D levels were 28.0 (interquartile range 20–38) ng/mL, with 16 patients (8.9%) having levels <12 ng/ml and 43 (23.9%) with 25(OH)D levels <20 ng/ml. No correlation was noted between levels of 25-hydroxyvitamin D and albumin-corrected calcium in the total group and in groups stratified by vitamin D supplementation.In contrast, both serum albumin(r = 0.32; P < 0.001) and MELD-Na scores were significantly correlated with 25-hydroxyvitamin D levels (r =–0.29; P < 0.001).Correlations between 25-hydroxyvitamin D levels and serum albumin (r =−0.39; P < 0.001) and MELD-Na scores did not change substantially after excluding 67 patients receiving vitamin D supplementation (r =−0.33; P = 0.009). In conclusion, total25-hydroxyvitamin D levels correlate inversely with liver disease severity in adults with cirrhosis.